IL-10-modulated dendritic cells from birch pollen- and hazelnut-allergic patients facilitate Treg-mediated allergen-specific and cross-reactive tolerance - Heinl, Patricia Vanessa; Graulich, Edith; Weigmann, Benno; Wangorsch, Andrea; Ose, Robert; Bellinghausen, Iris; Khatri, Rahul; Raker, Verena K.; Scheurer, Stephan; Vieths, Stefan; Saloga, Joachim; Steinbrink, Kerstin (Allergy, 2024)
Background: Approximately 70% of individuals allergic to birch pollen (Bet v 1.01 [Bet]) develop a secondary food allergy (e.g., hazelnut: Cor a 1.04 [Cor]), due to allergen cross-reactivity. However, standard immunotherapy for type I allergies often does not improve the food allergy sufficiently. We analyzed the allergen-specific and cross-reactive suppressive capacity of primary human regulatory T cells (Treg) induced by autologous IL-10-modulated dendritic cells (IL-10 DC) in vitro and in vivo. Methods: CD4+ T cells of patients with birch pollen and associated hazelnut allergies were differentiated into Bet-specific or non-specific induced Treg (iTreg). After Bet- or Cor-specific restimulation the phenotype, proliferation, and suppressive capacity of iTreg subsets were analyzed. iTreg function was further investigated in humanized mouse models of airway and intestinal allergy, generated by engraftment of peripheral blood mononuclear cells from allergic donors into immunodeficient animals. Results: After IL-10 DC priming and allergen-specific restimulation (Bet or Cor), non-specific control iTreg remained anergic, whereas Bet-specific iTreg proliferated extensively and exhibited a regulatory phenotype (enhanced expression of CTLA-4, PD-1, TNFR2, IL-10). Accordingly, activated Bet-specific iTreg displayed a high capacity to suppress Bet- and Cor-induced responder Th2 cell responses in vitro, indicating induction of both allergen-specific (birch) and cross-reactive tolerance (hazelnut). In vivo, the beneficial effect of Bet-specific iTreg was verified in humanized mouse models of allergic airway and intestinal inflammation, resulting in reduced allergen-induced clinical symptoms, and immune responses. Conclusion: Human IL-10 DC-induced iTreg facilitate allergen-specific and cross-reactive tolerance. Therefore, they are potential candidates for regulatory cell therapy in allergic and autoimmune diseases.
CRIS-Team Scopus Importer:2024-08-09
Keywords: bet v 1.01; cross-reactive tolerance; regulatory T cells; tolerogenic IL-10 DC; type I allergy